2021
DOI: 10.1186/s12967-021-03066-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circulating sphingosine kinase-related metabolites for prediction of type 2 diabetes

Abstract: Background Sphingosine Kinase (SphK) that catalyzes sphingosine (Sph) to sphingosine 1-phosphate (S1P), plays a key role in both sphingolipid metabolism and cellular signaling. While SphK has been implicated in type 2 diabetes mellitus (T2DM), it is unexplored in humans. Herein, we investigated whether circulating SphK-related metabolites are associated with T2DM incidence in an established prospective cohort. Methods Levels of SphK-related sphingo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This study analyzed two Chinese cohorts derived from a large Chinese population study, the Shanghai Changfeng Study, composing of 6,595 individuals consecutively enrolled from Shanghai Changfeng Community, Shanghai from June 2009 to December 2012 [ 19 ]. The inclusion criteria were age 45 years or older, and the exclusion criteria included refusal to participate in the study or refusal to sign an informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…This study analyzed two Chinese cohorts derived from a large Chinese population study, the Shanghai Changfeng Study, composing of 6,595 individuals consecutively enrolled from Shanghai Changfeng Community, Shanghai from June 2009 to December 2012 [ 19 ]. The inclusion criteria were age 45 years or older, and the exclusion criteria included refusal to participate in the study or refusal to sign an informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were age 45 years or older, and the exclusion criteria included refusal to participate in the study or refusal to sign an informed consent form. Initially, genome-wide DNA methylation profiles were measured in the whole blood of 100 participants with new-onset type 2 diabetes at follow-up examination (Cohort 1) as described previously [ 16 ] and a randomly sampled representative cohort of 407 participants (Cohort 2), who were selected using SPSS software by a computer. After excluding the participants with missing liver ultrasound examination, excessive alcohol consumption, or other known chronic liver diseases, 95 participants from Cohort 1 and 356 participants from Cohort 2 were included for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…On the most basic level, metabolomics can differentiate between healthy individuals and diseased individuals. 170,171 Studies [172][173][174][175] in humans have identified characteristic metabolic signatures of type II diabetes mellitus, obesity, and fatty liver disease. A consistent pattern of reduced glycine and acylcarnitines [176][177][178] with increased concentrations of valine, isoleucine, and α-hydroxybuterate 179,180 has been associated with both basal and dynamic measures of insulin resistance.…”
Section: Metabolomicsmentioning
confidence: 99%